FROM #XF6 TO #SERVIZIOPUBBLICO: CROSS-GENRE ANALYSIS OF TV AUDIENCE PARTICIPATORY PRACTICES IN ITALY - Boccia Artieri, Giovanni; Gemini, Laura; Giglietto, Fabio; Orefice, Mario (AoIR Selected Papers of Internet Research, 2014)
Trans-media usage practices, with a specific reference to the ones that imply strong correlation between TV viewing and online content production, are quickly becoming a fascinating field of study for scholars and practitioners. According to Nielsen, during 2013, about 36 million people sent out 990 million of Tweets about TV (Nielsen SocialGuide 2014). At the same time, growing number of studies focus on users’ communicative dynamics while watching specific TV programs or genres (Geerts and De Grooff 2009). From surveys about participatory viewing styles and repertoires (Mitchell et al. 2010, Cesar and Geerts 2011) to market-oriented researches (Proulx and Shepatin 2012), and more general attempts to go beyond Habermasian definition of public sphere (de Zúñiga, Jung, and Valenzuela 2012, Fuchs 2014). From media adoption perspective, Italy seems to be in line with general trend. Showing increasing shares both in TV viewing and Internet usage. In fact while, on the one side, average TV audience in a normal day raised of 1.8% from 2012 and “average time viewed” (the average daily time spent by every TV users) of 1.3% (Nielsen 2013), on the other side, total amount of people using social networking sites like Facebook and Twitter, wikis or traditional websites passed from 53,8% to 58,7% (+5%) during 2013 (Istat 2013). Despite this complex and interesting scenario, analyses and researches aimed at highlight some kind of correlations between different TV viewing styles and online contents actually represents an underestimated field of study. Opposite to this trend, this paper presents the first large-scale comparative study of Twitter contributors’ behavior in commenting two different types of TV format.